Teachers' Knowledge of Second Language and Curriculum: A Narrative Experience - Jenny Alexandra Mendieta Aguilar (Universidad Nacional de Colombia, 2011)
This study was carried out with a group of three teachers who work for the foreign languages department of a private university in Colombia. It was aimed at unveiling and characterizing the narrative knowledge these teachers hold about language teaching and learning processes as well as the role this knowledge plays in the constant construction and evaluation of curriculum. Data were collected through concept maps, biodata surveys, narrative interviews, and participant observation within a narrative inquiry approach to research. Findings show the crucial need to value and explore teachers' knowledge from a narrative perspective in order to better understand the complexity of the teaching context in which they work.